Buy Local and Social Interaction. Issue 4 (4th January 2021) - Winfree, Jason; Watson, Philip
Abstract : This paper examines the buy local movement using social interactions. Social interaction arises if some consumers have preferences for local economic output due to altruism toward local producers and/or because of local amenities that benefit the community. This introduces an incentive for some consumers to advocate for localism and convert other consumers to buy locally. However, when there are competing communities, global efforts to buy more local products leads to lower utility from consumption and, under some scenarios, no increases in local production. This paper analyzes the benefits and costs of buying locally under various types of localism and market structures.